The Roles of Clinical Psychologists in Burns Care: A Case Study Highlighting Benefits of Multidisciplinary Care - Anna V. Cartwright; Elizabeth Pounds-Cornish (MDPI AG, 2023)
The British National Burn Care Standards highlight the importance of routine psychosocial screening to optimise psychological well-being following burn injury. Routine screening enables clinicians to identify those who may benefit from further psychological intervention. In this case, we outline how active follow-up from routine psychosocial screening and early intervention supports psychological recovery from a burn injury and how multidisciplinary care can be incorporated into cognitive therapy for post-traumatic stress disorder. This case also illustrates how psychologists are well positioned within physical healthcare to notice themes arising in patient care and use this to inform service development, for example, through staff training.